Absolute Viscosities of Vegetable Oils at Different Temperatures and Shear Rate Range of 64.5 to 4835 s−1. (3rd August 2014) - Diamante, Lemuel M.; Lan, Tianying
Abstract : A study was carried out to determine the effect of higher shear rates (64.5 to 4835 s −1 ) on the absolute viscosities of different vegetable oils at different temperatures (26 to 90°C). The absolute viscosities of the different vegetable oils were determined using a Lamy Viscometer RM100, a rotating viscometer with coaxial cylinder. The torque of each sample at different temperatures was recorded at different shear rates. Based on the rheograms (plot of mean shear stress against shear rate), all of the vegetable oils studied were found to be Newtonian fluids. Rice bran oil was the most viscous (0.0398 Pa·s at 38°C) while walnut oil was the least viscous (0.0296 Pa·s at 38°C) among the oils studied. The higher shear range used did not significantly affect the absolute viscosities of the vegetable oils at the different temperatures. The absolute viscosities of the vegetable oils decreased with increasing temperature and can be fitted with an Arrhenius type relationship. The activation energies for the different vegetable oils ranged from 21 to 30 kJ/mole. The peanut and safflower oils had the highest and lowest activation energies, respectively. This means that greater energy was needed to effect a viscosity change in the peanut oil.